ENZA‐p trial protocol: a randomized phase II trial using prostate‐specific membrane antigen as a therapeutic target and prognostic indicator in men with metastatic castration‐resistant prostate cancer treated with enzalutamide (ANZUP 1901). (6th July 2021) - Emmett, Louise; Subramaniam, Shalini; Joshua, Anthony M.; Crumbaker, Megan; Martin, Andrew; Zhang, Alison Y.; Rana, Nisha; Langford, Ailsa; Mitchell, Jenna; Yip, Sonia; Francis, Roslyn; Hofman, Michael S.; et al.
Abstract : Objectives: To determine the activity and safety of lutetium‐177 ( 177 Lu)‐prostate‐specific membrane antigen (PSMA)‐617 in men with metastatic castration‐resistant prostate cancer (mCRPC) commencing enzalutamide, who are at high risk of early progression, and to identify potential prognostic and predictive biomarkers from imaging, blood and tissue. Participants and Methods: ENZA‐p (ANZUP 1901) is an open‐label, randomized, two‐arm, multicentre, phase 2 trial. Participants are randomly assigned (1:1) to treatment with enzalutamide 160 mg daily alone or enzalutamide plus 177 Lu‐PSMA‐617 7.5 GBq on Days 15 and 57. Two additional 177 Lu‐PSMA‐617 doses are allowed, informed by Day‐92 Gallium‐68 ( 68 Ga)‐PSMA positron emission tomography (PET; up to four doses in total). The primary endpoint is prostate‐specific antigen (PSA) progression‐free survival (PFS). Other major endpoints include radiological PFS, PSA response rate, overall survival, health‐related quality of life, adverse events and cost‐effectiveness. Key eligibility criteria include: biochemical and/or clinical progression; 68 Ga‐PSMA PET‐avid disease; no prior androgen signalling inhibitor, excepting abiraterone; no prior chemotherapy for mCRPC; and ≥2 high‐risk features for early enzalutamide failure. Assessments are 4 weekly during study treatment, then 6 weekly until radiographic progression. Response Evaluation Criteria in Solid Tumours (RECIST) are used to assess imaging conducted every 12 weeks, 68 Ga‐PSMA PET at baseline, Days 15 and 92, and at progression, and 18 F‐fluorine deoxyglucose ( 18 F‐FDG) PET at baseline and progression. Translational samples include blood (and optional biopsies) at baseline, Day 92, and first progression. Correlative studies include identification of prognostic and predictive biomarkers from 68 Ga‐PSMA and 18 F‐FDG PET/CT, circulating tumour cells and circulating tumour DNA. The trial will enrol 160 participants, providing 80% power with a two‐sided type‐1 error rate of 5% to detect a hazard ratio of 0.625 assuming a median PSA‐PFS of 5 months with enzalutamide alone. Results and Conclusion: The combination of 177 Lu‐PSMA‐617 and enzalutamide may be synergistic. ENZA‐p will determine the safety and efficacy of the combination in addition to developing predictive and prognostic biomarkers to better guide treatment decisions.